Preventing Sexual Violence in Senior High School: The Effect of Power of Act Training on Bystander Intervention - Arini Cantika Dewi; Muhammad Ilham Mudin; Febi Febriyanti; Bangkit Alamsyah; Sabirina Hajarani; Siti Nurbayani (Jurnal Pendidikan Ilmu Sosial, 2023)
Sexual violence in Indonesia is one of the biggest problems that must be addressed immediately, one of which is in the school environment. One of the efforts that can be done is to conduct bystander education training. The purpose of this study was to determine the effectiveness of bystander education named Power of Act to increase bystander behavior, decrease rape myth acceptance, increase empathy for victims, and decrease rape culture support. This study used a one group pretest-posttest design with three measurements (before the first intervention, after the second intervention, and 1 month follow-up since the second intervention). The study participants were 27 students in one high school class obtained from cluster random sampling. The results stated that students showed a significant increase in bystander behavior (p = 0.015) in the female sample as well as an overall significant decrease in rape myth acceptance (p = 0.001) until the follow-up test. Overall, Power of Act was found to have short-term effectiveness in increasing bystander behavior for women as well as decreasing rape myth acceptance. This program is expected to be one of the useful trainings in preventing sexual violence in high schools.